Development Trends of International Open Peer Review Platforms and Recommendations for China - ZHANG Zhixiong, WANG Yuju, ZHAO Yang (Nongye tushu qingbao xuebao)
[Purpose/Significance] This study systematically analyzes the basic models and development trends of international open peer review platforms, with the aim of exploring the insights these platforms provide for academic communication and research governance in China. The goal is to accelerate the establishment and development of an open peer review system in China, fostering a more open, collaborative, and efficient academic exchange environment that promotes the free flow of knowledge and the widespread dissemination of scientific ideas. [Method/Process] The article first reviews and analyzes several international open peer review platforms and communities that are led by the scientific community and operate independently of scientific journal publishing, such as Peer Community In (PCI), Sciety, PREreview, and Review Commons. On this basis, it outlines the basic operational models of international open peer review platforms and identifies a number of common features among the three basic models. Then, through an in-depth analysis of the development dynamics of these platforms and communities, the study summarizes their development trends from different perspectives, including research institutions, scientists, scientific community, and international academic communication models. Based on this analysis, and taking into account international experience and the specific characteristics of China's research environment, the article proposes recommendations for building an open peer review system in China. [Results/Conclusions] The study identifies three basic operational models of international open peer review platforms: platforms established for the purpose of open publishing, platforms developed primarily as preprint servers, and platforms built independently for open peer review. It also summarizes the key trends in the development of these platforms: strong support from major research institutions, active participation of leading scientists, the formation and impact of large-scale platforms, recognition of open peer-reviewed research by the scientific community, alignment with the international open access (OA) movement, and the reshaping of international academic communication models.International open peer review platforms and communities are emerging as important forces in driving research innovation and enhancing research quality. In light of China's current situation, the article offers six recommendations to accelerate the development of open peer review platforms and communities: (1) fully recognizing the significance of open peer review platforms for Chinese science; (2) updating scientific publishing concepts to create a supportive environment for the development of open peer review platforms; (3) implementing policies to support the construction of open peer review platforms and communities in China; (4) promoting exemplary cases and innovative practices in the development of open peer review platforms and communities; (5) building robust national open peer review infrastructure to support the development of open peer review communities; and (6) engaging in brand building to create internationalized open peer review platforms and communities. These efforts aim to secure a new position for China in global scholarly communication.